PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PT. PLN (PERSERO) DISTRIBUSI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA - Rivaldi Idris; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2018)
Human resources are one of the resources that belong to the company, where the human resources have a very important factor in the success of the company's effort to create a good performance, because the company had though funding sources the great and the good infrastructure and facilities, but when humans working on tasks within his do not contribute with good then it will be difficult for the company to create a good performance. This research aims to know the influence of work environment on performance of employees through the motivation of working as an intervening variable in pt. PLN (Persero) distribution of Central Java and Yogyakarta. This research type is explanatory research. The sampling techniques used in this research is the technique of Probability Sampling and its kind are Proportionate Stratified Random Sampling. The number of samples taken in this study as many as 101 respondents. In this study, assisted by computer programs to process data that is SPSS 22.0. The results obtained in this study indicate that the independent variable has a positive and significant influence towards the dependent variable, either partially or simultaneous. While the variable interbening used in this research showed there is an indirect influence of variables the dependent variable and independent of a partial mediation. Suggestions in this study was the need to improve relationships between employees in a non physical company. The company must also be able to create competition between employees, so that employees can be more motivated in their work. In addition, the company must conduct the evaluation in terms of the accuracy of the time of employees in work performance, so that the karyawaan can be better again.